PENGARUH TIPE BIOMASSA PADA PRODUK PIROLISSI: A REVIEW: Effect of Biomass Types on Products of Pyrolysis: A Review - Nur Aini; Siti Jamilatun; Joko Pitoyo (Agroindustrial Technology Journal, 2022)
The exploitation of fossil energy causes non-renewable reserves to dwindle and causes global warming; climate change endangers living things. Energy sources from the second generation, namely lignocellulosic-based biomass, provide development opportunities, not interfere with food reserves, and are easy to cultivate. One technology that is feasible to use to treat lignocellulosic biomass is pyrolysis. Pyrolysis can convert lignocellulosic biomass (including lignin, cellulose, and hemicellulose) into solid, liquid, and gaseous. The pyrolysis mechanism by thermal decomposition goes through several stages, namely charcoal formation, depolymerization, fragmentation, and other secondary reactions. This paper provides insight into the pyrolysis of lignocellulose and its by product. Several parameters, equivalent to reaction environment, temperature, residence time, and heating rate, considerably have an effect on the pyrolysis process. The results of the pyrolysis of various biomass with certain operating conditions obtained yields/products in the form of Bio-oil, Gas and Bio-char with different percentages depending on the treatment.